Web-Based Procurement Information System at CV Radra Sejahtera - Rafly Farrelsyah (Journal of Information System and Artificial Intelligence, 2025)
From field observations, the process of submitting procurement requests for goods and services at CV Radra Sejahtera is still conducted offline and has not been well-organized. Currently, clients requiring procurement must first send a formal letter to CV Radra Sejahtera, which is then processed by the company. This approach is considered slow due to the absence of an integrated system that allows clients to submit requests directly. This study aims to develop a system that facilitates the connection between CV Radra Sejahtera and its clients or users online. With this system, clients can directly submit their procurement needs without the need for manual letter submissions. The objective of this research is to build an information system that assists in the submission and management of goods and services procurement at CV Radra Sejahtera. The system is designed and developed as a web-based platform using the Extreme Programming (XP) methodology. XP is chosen due to its advantages in shortening development time and simplifying bureaucratic processes, thereby accelerating the procurement request process. Based on the research findings, the developed system improves time efficiency by 50% in the request submission process. Previously, the submission process took an average of two days, but with the system, clients can complete their procurement requests in less than one day. Therefore, this system greatly benefits both the clients and CV Radra Sejahtera.